PENGARUH EDUKASI VAKSIN COVID-19 TERHADAP PENGETAHUAN DAN PERUBAHAN SIKAP MASYARAKAT TENTANG KEAMANAN VAKSIN COVID-19 DI KECAMATAN KOJA - Annisa Rizky Arifiani (2022)
Communication or messages that are noticed, understood, and received are an important key in education that can change the cognitive, affective, and conative sides. The message design used in this study shows the positive sides of the Covid-19 vaccine. The purpose of this study was to determine the effect of Covid-19 vaccine education on knowledge and changes in public attitudes about the safety of the Covid-19 vaccine in Koja District. The method used in this study is pre-experimental with a one-group pre-test and post-test design because this design is considered more accurate in controlling treatment events so that it is possible to make comparisons before being given treatment. This research was conducted in the Koja District area by involving 100 respondents who were distributed through questionnaires, from the results of the initial test, the knowledge of the Koja District community was in a low category, then after being given the Covid-19 vaccine education treatment using the lecture method the results could increase to a high category. Then the results of the initial test on the attitude of the people of Koja District have shown a positive attitude (favorable) after being given treatment then the positive attitude becomes more increased. The conclusion of the study shows that there is an effect of Covid-19 vaccine education on knowledge and changes in public attitudes about the safety of the Covid-19 vaccine in Koja District.